2000
DOI: 10.1046/j.1526-4610.2000.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Predictive Factors in the Evolution of Episodic to Chronic Cluster Headache

Abstract: The purpose of our study was to identify general factors and distinctive clinical features differentiating patients with chronic cluster headache (CH) evolved from episodic CH and patients with episodic CH. Our study sample included 28 patients suffering from chronic CH evolved from episodic CH and 258 patients with episodic CH; all were referred to the Headache Center of Parma between December 1975 and June 1998. Patients with episodic CH were selected from all episodic CH referrals (n = 485) and selection wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 34 publications
7
19
1
Order By: Relevance
“…The results of our investigation are similar to those in literature [6,11,13,14,27,38,39] with regard to the prevalence of males and smokers, the long duration of the disorder, and the data indicating that the majority of patients (over 90%) began to smoke before the beginning of CH. In Italy there has been a decline of smoking prevalence for both sexes since 1990 [40].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of our investigation are similar to those in literature [6,11,13,14,27,38,39] with regard to the prevalence of males and smokers, the long duration of the disorder, and the data indicating that the majority of patients (over 90%) began to smoke before the beginning of CH. In Italy there has been a decline of smoking prevalence for both sexes since 1990 [40].…”
Section: Discussionsupporting
confidence: 91%
“…This high prevalence of smokers, greater than in the general population [7], supports the possibility that smoking may trigger the development of CH [10-12]. In favour of a causal relationship between smoking and CH, it has been observed that in most cases the onset of the smoking habitus precedes the beginning of CH [6,8,13-15] and that the prolonged exposure to second hand smoke during childhood may trigger CH even in non-smokers [12,16]. Moreover, CH develops earlier in people living with smoking parents [12].…”
Section: Introductionmentioning
confidence: 89%
“…Most clinical characteristics of CH reported in this study are consistent with other studies from Western and Eastern regions in the world, which included gender dominance for male [4-15,17-22], similar age at onset [5-7,9,13-15,18,19], temporal or retro-orbital regions as common sites of pain [5,7,13-15], lacrimation as the most frequent autonomic feature [5,7,13-15], high frequencies of migrainous features, low frequency of positive family history and seasonal propensity in spring and autumn (Table 7). Yet, it is also worth noting some discrepancies between the current and previous results.…”
Section: Discussionsupporting
confidence: 90%
“…Chronic cluster headache accounts for 10-21% of all cluster headaches, [3,10,11] but is rare in the Taiwanese and Asians, [12] with Case 13 in the present series being the fi rst case of chronic cluster headache ever reported in Taiwan. [13] Interestingly, she did not have a good response to topiramate treatment until the dose was reached 400 mg/day.…”
Section: Discussionmentioning
confidence: 83%